Editorial: Environmental Issues and Globalization: A Three State-Market Approaches - Mahayasa, Dias Pabyantara Swandita (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2024)
Environmental Issues and Globalization: A Three State-Market Approaches